1990
DOI: 10.1016/s0022-5347(17)39908-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Gene Analysis in Renal Cell Carcinoma

Abstract: The epidermal growth factor receptor binds the mitogens epidermal growth factor and transforming growth factor-alpha. Increased expression of the epidermal growth factor receptor has been noted in many types of tumors and is associated with gene amplification in several including epidermoid carcinoma, lung carcinoma, breast carcinoma and glioblastoma. We have recently observed increased expression of the epidermal growth factor receptor messenger RNA in neoplastic tissue relative to normal kidney tissue from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…We suggest that VHL-null cells engage in an HIF-dependent constitutive activation of the TGF-␣/EGF-R growth stimulatory pathway and that this constitutes the postulated gatekeeper function of VHL in renal epithelial cells (9,10,64,65). This model is founded on experiments focusing on the ability of VHL Ϫ/Ϫ RCC cells to proliferate in the absence of exogenous growth factors, whereas primary cultures of renal epithelial cells require addition of exogenous growth factors, or serum, to proliferate in culture (66,67). The ability of transformed cells to engage in an autonomous growth stimulatory pathway has been appreciated in several types of cancers and is one of the accepted hallmarks of cellular transformation (35-38, 68 -70) Our model of HIF-mediated activation of the TGF-␣/EGF-R pathway as a major oncogenic pathway in VHL Ϫ/Ϫ RCC cells is supported by the following: First, we show in this report that inhibition of EGF-R phosphorylation and of serum-independent growth of VHL Ϫ/Ϫ RCC can be achieved to a similar extent by either reintroducing VHL function, by abolishing HIF activation or by inhibiting EGF-R activity.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that VHL-null cells engage in an HIF-dependent constitutive activation of the TGF-␣/EGF-R growth stimulatory pathway and that this constitutes the postulated gatekeeper function of VHL in renal epithelial cells (9,10,64,65). This model is founded on experiments focusing on the ability of VHL Ϫ/Ϫ RCC cells to proliferate in the absence of exogenous growth factors, whereas primary cultures of renal epithelial cells require addition of exogenous growth factors, or serum, to proliferate in culture (66,67). The ability of transformed cells to engage in an autonomous growth stimulatory pathway has been appreciated in several types of cancers and is one of the accepted hallmarks of cellular transformation (35-38, 68 -70) Our model of HIF-mediated activation of the TGF-␣/EGF-R pathway as a major oncogenic pathway in VHL Ϫ/Ϫ RCC cells is supported by the following: First, we show in this report that inhibition of EGF-R phosphorylation and of serum-independent growth of VHL Ϫ/Ϫ RCC can be achieved to a similar extent by either reintroducing VHL function, by abolishing HIF activation or by inhibiting EGF-R activity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many investigations revealed an increased expression of EGF-R in RCC compared with normal renal tissue [14,15,17,[21][22][23][24][25], Additionally, arbitrary immunohistochemical staining intensity [23] or bioreactive EGF-R content [25] were reported to be pre dictive for clinical progression in RCC. In contrast, in the study of Fjungberg et al [24] no relevance of EGF-R mRNA expression on prognosis was observed.…”
Section: Prognostic Impact Of the Coexpression Of The Factors Studiedmentioning
confidence: 99%
“…However, most investigators have not detected EGF in tumor tissue from patients with RCC [35]. Overexpression of the EGF receptor has been reported by several authors [35,36,37]. Elevated levels of transforming growth factor-α (TGF-α) have been observed in VHL-deficient cancer cells [38].…”
Section: Sporadic Rccmentioning
confidence: 99%